INNATE TL1A SIGNALING PROMOTES INTESTINAL NEUTROPHIL ACTIVATION AND COLITIS ASSOCIATED CANCER. (26th January 2023) - Pires, Silvia; Yang, Wei; Longman, Randy
Abstract: Intestinal inflammation associated with chronic inflammatory bowel disease (IBD) increases the risk of developing colitis-associated cancer (CAC), but the cellular mechanisms driving CAC are not well defined. Polymorphisms in TNFSF15 (called TNF-like cytokine 1a or TL1A) are highly associated with IBD and the aim of this work is to evaluate a potential mechanistic role of TL1A in regulating CAC. Data from the human atlas protein database revealed that TL1A protein is present in 50% of colorectal cancer tissue samples and that high expression of TNFSF15 correlated with reduced survival. To test the functional role for TL1A in tumorigenesis, we used the well-established AOM/DSS model of CAC in mice deficient for the TL1A receptor (called death receptor 3 or DR3) and mice deficient for myeloid derived TL1A (CD11C cre + TNFSF15 fl/fl ). We found that both DR3-deficient mice and myeloid derived TL1A deficient mice had a significant reduction in tumor number compared to heterozygous littermate controls. To evaluate the contribution of innate lymphocytes, we used DR3-deficient mice on a RAG-deficient background in our AOM/DSS model. Even in the absence of B and T cells, DR3-deficient mice still showed significant reduction in tumor burden, suggesting innate lymphoid cell (ILC) contribution. DR3-deficient mice also revealed a significant reduction in neutrophil infiltration. Neutrophil depletion with α-Ly6G similarly resulted in a significant reduction of tumor numbers in our CAC model in a DR3 dependent manner. To test the direct regulation of neutrophils by ILCs, we establish a co-culture model. TL1A activated ILCs triggered neutrophil activation (CD177) and maturation (CD11B) which required GM-CSF. In vivo activation with a DR3 agonist confirmed intestinal ILC3 production of GM-CSF but also impacted bone marrow granulopoiesis by expanding both mature neutrophils and granulocyte-macrophage progenitors (GMPs). CONCLUSION: Our data reveals a new link between intestinal ILC production of GM-CSF and neutrophil activation that promotes CAC and bone marrow granulopoiesis.